Urox containing concentrated extracts of Crataeva nurvala stem bark, Equisetum arvense stem and Lindera aggregata root, in the treatment of symptoms of overactive bladder and urinary incontinence: a phase 2, randomised, double-blind placebo controlled trial - Niikee Schoendorfer; Nita Sharp; Tracey Seipel; Alexander G. Schauss; Kiran D. K. Ahuja (BMC, 2018)
Abstract Background Storage lower urinary tract symptoms (LUTS) including overactive bladder (OAB) and urinary incontinence (UI) affect millions of people worldwide, significantly impacting quality of life. Plant based medicines have been documented both empirically and in emerging scientific research to have varying benefits in reducing bladder symptoms. We assessed the efficacy of Urox®, a proprietary combination of phytomedicine extracts including, Cratevox™ (Crataeva nurvala) stem bark, Equisetem arvense stem and Lindera aggregata root, in reducing symptoms of OAB and UI. Methods Efficacy of the herbal combination on a variety of bladder symptoms compared to an identical placebo, were documented in a randomised, double-blind, placebo controlled trial conducted at two primary care centres. Data were collected at baseline, 2, 4 and 8 weeks, with the primary outcome being self-reported urinary frequency. Statistical analysis included mixed effects ordered logistic regression with post hoc Holm's test to account for repeated measures, and included an intention-to-treat analysis. Results One hundred and fifty participants (59% female, aged; mean ± SD; 63.5 ± 13.1 years) took part in the study. At week 8, urinary day frequency was significantly lower (OR 0.01; 95%CI 0.01 to 0.02; p < 0.001) in response to treatment (mean ± SD; 7.69 ± 2.15/day) compared to placebo (10.95 ± 2.47/day). Similarly, episodes of nocturia were significantly fewer (OR 0.03; 95%CI 0.02 to 0.05) after 8 weeks of treatment (2.16 ± 1.49/night) versus placebo (3.14 ± 1.36/night). Symptoms of urgency (OR 0.02; 95%CI 0.01 to 0.03), and total incontinence (OR 0.03; 95% CI 0.01 to 0.06) were also lower (all p < 0.01) in the treatment group. Significant improvements in quality of life were reported after treatment in comparison to placebo. No significant side effects were observed resulting in withdrawal from treatment. Conclusions The outcome of this study demonstrated both statistical significance and clinical relevance in reducing symptoms of OAB, urinary frequency and/or urgency and incontinence. The demonstrated viability of the herbal combination to serve as an effective treatment, with minimal side-effects, warrants further longer term research and consideration by clinicians. Trial registration NCT02396160 (registered on 17 March 2015 - before any statistical analyses commenced).